Alveolar macrophage dysfunction and cytokine storm in the pathogenesis of two severe COVID-19 patients - Wang, Chaofu (EBioMedicine, 2020)
BACKGROUND: The novel coronavirus pneumonia COVID-19 caused by SARS-CoV-2 infection could lead to a serious of clinical symptoms and severe illness, including acute respiratory distress syndrome (ARDS) and fatal organ failure. We report the fundamental pathological investigation in the lungs and other organs of fatal cases for the mechanistic understanding of severe COVID-19 and the development of specific therapy in these cases. METHODS: The autopsy and pathological investigations of specimens were performed on bodies of two deceased cases with COVID-19. Gross anatomy and histological investigation by Hematoxylin and eosin (HE) stained were reviewed on each patient. Alcian blue/periodic acid-Schiff (AB-PAS) staining and Masson staining were performed for the examinations of mucus, fibrin and collagen fiber in lung tissues. Immunohistochemical staining were performed on the slides of lung tissues from two patients. Real-time PCR was performed to detect the infection of SARS-CoV-2. Flow cytometry analyses were performed to detect the direct binding of S protein and the expression of ACE2 on the cell surface of macrophages. FINDINGS: The main pathological features in lungs included extensive impairment of type I alveolar epithelial cells and atypical hyperplasia of type II alveolar cells, with formation of hyaline membrane, focal hemorrhage, exudation and pulmonary edema, and pulmonary consolidation. The mucous plug with fibrinous exudate in the alveoli and the dysfunction of alveolar macrophages were characteristic abnormalities. The type II alveolar epithelial cells and macrophages in alveoli and pulmonary hilum lymphoid tissue were infected by SARS-CoV-2. S protein of SARS-CoV-2 directly bound to the macrophage via the S-protein-ACE2 interaction. INTERPRETATION: Infection of Alveolar macrophage by SARS-CoV-2 might be drivers of the “cytokine storm”, which might result in damages in pulmonary tissues, heart and lung, and leading to the failure of multiple organs . FUNDING: Shanghai Guangci Translational Medical Research Development Foundation, Shanghai, China